Ästhetik und Verkehr. Erste empirische Ergebnisse. - Evangelinos, Christos; Matthes, Andreas; Stirl, Mario; Wieland, Bernhard (Deutscher Verkehrs-Verl., 2010)
In der Ausgabe Internationales Verkehrswesen 12/2008 wurde in einem Beitrag mit dem Titel "Ästhetik und Verkehr" für eine monetäre Erfassung der ästhetischen Gewinne und Verluste von Verkehrsbauwerken plädiert. Der Artikel macht die Probe aufs Exempel und beschreibt eine entsprechende empirische Studie zur Dresdner Waldschlösschenbrücke.

The paper attempts to monetize aesthetical preferences for the Waldschlösschenbrücke in Dresden. We use the Waldschlösschenbrücke as one of the most prominent examples of the significance of aesthetical aspects in transport infrastructure, which can have far-reaching consequences, since Dresden lost (due to the bridge) its UNESCO World Heritage status. Using data from a stated preference survey, we calculate the willingness to pay and willingness to accept for a total of five alternatives: three types of bridge, a tunnel solution, and the status quo (no bridge). It comes, perhaps, as no surprise that the finally implemented type of bridge shows the highest willingness to pay among the three types of bridge. More interestingly, we find that in total the bridge construction entails aesthetical net losses of yearly EUR 6.1 million. A comparison of this amount with the value of travel time savings results in two Euros aesthetical losses for one Euro travel time savings.
Aesthetics and transport - first empirical results.
Keywords: Verkehr; Verkehrsbauwerk; Brücke; Entwurf; Ästhetik; Befragung; Bewohner; Kosten-Nutzen-Analyse; Tunnel; Weltkulturerbe; Empirische Untersuchung; Präferenz; Gestaltung; Tourist